Implicit Pedagogical Alignment with van Hiele Theory in Geometry Learning: Teachers’ Understanding, Instructional Practices, and Assessment - Nur'aini Muhassanah; Ariyadi Wijaya; Syukrul Hamdi; Heri Retnawati; Wahyu Setyaningrum; Novi Andri Nurcahyono (CV. Samuel Manurung and Co, 2026)
Teachers’ understanding of students’ geometric thinking is essential for designing geometry instruction that supports cognitive development. Although previous studies have demonstrated the effectiveness of van Hiele-based instruction, little is known about how teachers understand and enact its principles in classroom practice. This study explored junior secondary mathematics teachers’ understanding of the van Hiele theory, their perceptions of students’ geometric thinking levels, the instructional strategies they employ, and their assessment practices in geometry learning. A qualitative phenomenological approach was conducted with eleven junior secondary mathematics teachers selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings indicate that teachers have limited formal understanding of the terminology and hierarchical structure of the van Hiele theory. Nevertheless, they demonstrate implicit pedagogical alignment with its principles through their classroom practices. Teachers were able to identify students’ geometric thinking, particularly at the visualization and analysis levels, and employed concrete and visual representations, exploratory learning, classroom discussion, questioning, and contextual problem-solving to support students’ learning. Assessment practices included oral questioning, written tasks, observations, presentations, and formative assessment, although assessment of higher-order geometric reasoning remained limited. These findings suggest that teachers’ professional experience can foster pedagogical practices consistent with van Hiele’s principles despite limited theoretical mastery. The study contributes empirical evidence of implicit pedagogical alignment and highlights the importance of professional development that integrates teachers’ practical experience with a systematic understanding of geometric thinking.